Finding alternative roles for Traditional Birth Attendants: an experience from the south of Angola. (13th November 2019) - Fattorini, M; Raguzzoni, G; Cuccaro, C; Nante, N; Quercioli, C; Ileni, F; Kaunawoye, M C; Caresia, C; Putoto, G
Abstract: Background: Reduction of maternal mortality ratio (MMR), a key indicator contained in the Sustainable Development Goals (SDGs), is strictly related to maternal empowerment and to an increasing access to skilled care in pregnancy, childbirth and postpartum. The WHO recommends to define alternative roles for Traditional Birth Attendants (TBAs) in the transition from birth with TBAs to birth with Skilled Birth Attendants (SBAs), in particular in countries where maternal care services still do not meet recommended standards. Objectives: In 2018, the Italian Non-Governmental Organization Doctors with Africa CUAMM and the District Health Department of Ombadja (a 350000 inhabitants district in Cunene province, south of Angola) started a three-year multifaceted project to support and strengthen local health services. Aim of this work is to describe the first six months of an implemented activity involving 120 local TBAs, identified and trained to perform basic educational talks in the district territory regarding topical issues of mother and child health. TBAs were also engaged in the referral of pregnant women to health facilities with SBAs. Results: From June to November 2018, TBAs performed 2272 talks about maternal and child health issues: healthy pregnancy (551 talks, 24.3%), nutrition (404, 17.8%) and malaria (370, 16.3%) were the most debated topics. The total of women's presences during these educational talks was 57504, and 15379 of them (26.7%) were pregnant. TBAs referred to health facilities 226 pregnant women for a delivery assisted by SBAs. Conclusions: Angolan estimated MMR in 2015 was 477/100000 live births: therefore, more efforts should be made to contribute to the achievement of 2030 SDGs target of 70/100000 globally. Moreover, the country percentage of deliveries assisted by SBAs is less than 50%. Promoting alternative roles for TBAs into the mother and child health framework could represent an effective way to improve maternal and neonatal outcomes. Key messages: According to the World Health Organization, defining alternative roles for traditional birth attendants could represent an effective way to support the health of women and children. Traditional Birth Attendants can play an important role in providing basic health education and in the "referral chain" of pregnant women to health facilities with skilled birth attendants.